2001
DOI: 10.1086/318809
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1/2 Clinical Trial of Enzyme Replacement in Fabry Disease: Pharmacokinetic, Substrate Clearance, and Safety Studies

Abstract: Fabry disease results from deficient alpha-galactosidase A (alpha-Gal A) activity and the pathologic accumulation of the globotriaosylceramide (GL-3) and related glycosphingolipids, primarily in vascular endothelial lysosomes. Treatment is currently palliative, and affected patients generally die in their 40s or 50s. Preclinical studies of recombinant human alpha-Gal A (r-halphaGalA) infusions in knockout mice demonstrated reduction of GL-3 in tissues and plasma, providing rationale for a phase 1/2 clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
245
1
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(257 citation statements)
references
References 14 publications
6
245
1
5
Order By: Relevance
“…Patients lacking expression of LAMAN1, 3, 6 may develop antibodies against the recombinant enzyme affecting ERT efficacy. However, in this first clinical study for alpha‐mannosidosis the frequency of infusion‐related reactions as well as the production of antibodies against the recombinant enzyme was low19 in comparison with other ERT studies 50, 51, 52, 53, 54. Furthermore, these rhLAMAN‐specific antibodies were shown not to be neutralizing, suggesting only mild immunological complications with regard to future ERT.…”
Section: Discussioncontrasting
confidence: 55%
“…Patients lacking expression of LAMAN1, 3, 6 may develop antibodies against the recombinant enzyme affecting ERT efficacy. However, in this first clinical study for alpha‐mannosidosis the frequency of infusion‐related reactions as well as the production of antibodies against the recombinant enzyme was low19 in comparison with other ERT studies 50, 51, 52, 53, 54. Furthermore, these rhLAMAN‐specific antibodies were shown not to be neutralizing, suggesting only mild immunological complications with regard to future ERT.…”
Section: Discussioncontrasting
confidence: 55%
“…patients with non-specific neuropathic pain, AK or CV but without heart or kidney involvement), a skin biopsy with characteristic storage on electron microscopy (EM) could confirm the diagnosis of FD. The presence of characteristic storage in the skin has been well documented in most classical male FD patients (Eng et al 2001;Thurberg et al 2004), while reports on skin biopsies in nonclassical FD patients, i.e. who have confirmed storage in a kidney or heart biopsy but not fulfilling the criteria for a definite classical diagnosis of FD (Table 1), are lacking.…”
Section: Pathologymentioning
confidence: 99%
“…With advancing age, vascular disease of the heart, kidneys, and brain leads to early demise, typically in the fourth and fifth decades of life. Currently, there is no specific treatment for Fabry disease, but recent animal and human clinical trials have indicated the feasibility of recombinant enzyme replacement therapy (Ioannou et al 2001;Eng et al 2000Eng et al , 2001.…”
Section: Introductionmentioning
confidence: 99%